The stratigraphy separation diagram–an amazing tool for fault analysis - Knížek, M.; Melichar, R.; Janečka, J. (TRABAJOS DE GEOLOGÍA, 2009)
The Stratigraphy Separation Diagram (SSD) is a neglected tool of fault analysis, which allows the interpretation of both fault-surface geometry and the mechanism of faulting. As it needs to evaluate displacement (separation) along the fault under study, this method can be used only in areas with well-documented (tectono)-stratigraphic sequences. The paper presents both some common patterns of SSD and two examples of seemingly similar faults from the Barrandian area (Czech Republic).